Serum homocysteine as a predictor of severity of peripheral arterial disease in association with Doppler ultrasonography - S. P., Preethi; Hemachandran, Tejaswi (International Surgery Journal, 2019)
Background: To evaluate association between raised serum homocysteine levels and severity of peripheral vascular disease (PVD) and to assess the role of homocysteine as a prognostic marker in PVD and thereby aid in early referrals to prevent cerebral and coronary events in those patients and introduce homocysteine lowering with vitamin therapy as part of medical management in patients diagnosed with PVD. Methods: The serum homocysteine levels was measured in all patients admitted for peripheral vascular disease of upper and/or lower limb and to correlate the above values with Doppler ultrasonography (USG) in the duration between 2016-2018 (18 months). Results: The comparison of homocysteine levels with Doppler shows corresponding significant increase in Serum Hcy levels only in cases of moderate PVD. Statistical analysis with binary logistic regression does show a significant association with moderate severity of PVD and serum homocysteine levels with 66.7% predictability. Conclusions: There was significant association of homocysteinemia only in Moderate PVD with no statistically significant correlation with mild, severe cases of peripheral arterial disease (PAD) and radiological normal cases, further large randomised trials are required to elucidate its clinical relevance in PAD as a prognostic marker of severity.